Efficacy and Side Effects of Aripiprazole and Olanzapine in Patients with Psychotic Disorders: A Randomized Controlled Trial - Nima Ghitoli; Leeba Rezaie; Adele Elahi (Oman Medical Journal, 2023)
Objectives: In clinical experience, selecting atypical antipsychotics optimally balancing their benefits and potential side effects is seen to improve treatment adherence in patients. This study aimed to compare the effectiveness and side effect profiles of aripiprazole and olanzapine in patients with psychotic disorders. Methods: In this double-blind clinical trial, the subjects were patients with psychotic disorders treated with aripiprazole and olanzapine. The subjects were randomly divided into two equally sized groups. One group was treated with olanzapine and the other group with aripiprazole. All participants were assessed using the positive and negative syndrome scale and side effects were monitored over a two-month follow-up period. Results: The participants comprised N = 76 patients (65 male; 11 female). Treatments with both aripiprazole (n = 38) and olanzapine (n = 38) were associated with a significant decrease in the severity of psychotic symptoms over the two-month treatment period. This decrease was achieved faster in the olanzapine group. There were no significant differences in the changes in body mass index, waist circumference, blood sugar, triglyceride, or cholesterol between the two groups. A qualitative difference between the groups was found in their total sleep duration. Conclusions: Olanzapine was more effective than aripiprazole in reducing psychotic symptoms. There were no significant differences between the overall side effect profiles of the two drugs.